Optimasi Pemanfaatan LPG Sebagai Bahan Bakar Genset Untuk Mendukung Program Penghematan Energi - yovan witanto; Benny Dwika Leonanda (Politeknik Negeri Padang, 2023)
The use of LPG as a generator fuel needs to be optimized. For this reason, the correct LPG gas flow rate needs to be studied so that it becomes economical. The purpose of this study is to analyze the effect of fuel flow rate variation and Choke Valve variation on the performance of a 4-stroke generator. Gas enters the carburetor with varying gas flow rates of 3 L/minute, 4 L/minute, 5 L/minute and 6 L/minute. Then the generator is set to run stably on fully open, half and closed Choke Valve variations. From these variations, a combination is then sought to produce the smallest LPG flow rate with optimum power. The generator can operate well at flow rates of 4 L/min and 5 L/min with the Choke Valve variation position fully open. This shows that the ratio of LPG and air reaches the ideal condition so that the combustion process is complete. Optimization of LPG consumption in the generator is set at a flow rate of 4 L/minute with the Choke Valve fully open. Thus the excessive use of LPG can be saved.